Adsorption studies of benzene and toluene in gas phase onto activated carbon fabrics in fixed bed column - Razieh Salehi; Fatemeh Dadashian; Mohammad Abedi; Ali Eliassi (Heliyon)
The application of Activated Carbon Fabrics for adsorption of gas contaminants, including Benzene and Toluene, was performed in a fixed bed column at room temperature. The effect of process parameters such as initial inlet concentration, flow rate, and adsorbent mass on the efficiency of the column was evaluated. Results indicated that increasing adsorbent mass and decreasing initial toluene concentration increase adsorption capacity and breakthrough time. Doubling the adsorbent mass led to an increase in breakthrough time from 48 min to 132 min and from 147 min to 340 min. Reducing the flow rate causes the adsorption capacity and the breakthrough time to increase. The adsorption capacity of toluene is always higher than that of benzene, which can be explained by the higher relative pressure of toluene compared to benzene, which has increased the adsorption capacity. Experimental data were analyzed using the Adams–Bohart, Thomas, and Yoon-Nelson models. The Thomas and Yoon-Nelson models, with correlation coefficients above 0.9, effectively predicted gas adsorption performance in a fixed bed column. However, the Yoon-Nelson model cannot correctly predict the data's behavior in the early moments. It can be seen, in general, that the Thomas model is well able to describe the behavior of the data.